Self-Management in Married Students (Case Study on BKPI Students UIN Antasari Banjarmasin) / Manajemen Diri pada Mahasiswa yang Sudah Menikah (Studi Kasus Pada Mahasiswa Program Studi BKPI UIN Antasari Banjarmasin) - Widiya Radiani; Muhammad Khaitami A (Alhiwar: Jurnal Ilmu dan Teknik Dakwah)
This research is motivated by the phenomenon of dual roles faced by married students, particularly in managing their studies and household responsibilities. This issue draws attention because the increasing academic and domestic demands often trigger stress and require good self-management. This research aims to explore how self-management is applied by married students. The method used in this research is qualitative with a case study approach. Data collection was conducted through in-depth interviews and observations of two married female students at the State Islamic University of Antasari Banjarmasin. The research results show that married students can demonstrate good self-management through aspects of self-motivation, self-organization, self-control, and self-development. The subject successfully balanced household duties and studies with the support of their partner and the ability to manage time and tasks efficiently.